An ultraviolet-proof car window film and a preparation method thereof
Patent Information
- Application Number
- CN202510439848.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-04-09
AI Technical Summary
紫外线长时间照射会导致皮肤晒伤,长期暴露在紫外线下有很大的健康风险,且紫外线的照射会加速内饰老化,影响车辆的长期使用
[0019]本发明在制备防紫外汽车车窗贴膜时,将1-H-吡咯-3-甲醇、吡咯反应后再与二氯化烯丙基膦反应制得改性聚吡咯颗粒;甲基环四硅氧烷、八甲基环四硅氧烷、3-缩水甘油丙基(二甲氧基)甲基硅烷、1,3-双(3-氨基丙基)-1,1,3,3-四甲基二硅氧烷反应制得改性聚硅氧烷;将苯并[1,2-d:5,4-d']二(噁唑)-2,6-二硫醇与4-氨基苯甲酰氯反应制得改性紫外吸收剂;将异佛尔酮二异氰酸酯、聚四氢呋喃醚二醇、二月桂酸二丁基锡、改性聚吡咯颗粒、改性聚硅氧烷、改性紫外吸收剂、氯铂酸反应并于模具中铺平,制得防紫外汽车车窗贴膜。
Smart Images

Figure BDA0005350725390000031 
Figure BDA0005350725390000101 
Figure BDA0005350725390000111
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials, specifically to an anti-ultraviolet automotive window film and its preparation method. Background Technology
[0002] Car window tinting involves applying a thin film to the front and rear windshields, side windows, and sunroof of a vehicle. The main functions of car window tinting are to block ultraviolet rays, reduce heat, prevent injury from flying glass, and reduce glare.
[0003] As living standards improve, people's demands for quality of life are also increasing, leading to more diverse requirements for car window tinting. Prolonged exposure to ultraviolet (UV) radiation can cause sunburn and poses significant health risks. Furthermore, UV radiation accelerates interior aging, affecting the long-term use of the vehicle. Infrared radiation is a major source of heat, causing significant temperature increases inside the car, affecting not only interior comfort but also posing a serious safety hazard. The UV-resistant automotive window tinting film prepared in this invention possesses excellent UV protection, heat insulation, flame retardancy, anti-aging properties, and good mechanical properties, indicating a promising market prospect. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing waterproof and stain-resistant wall coverings to solve the problems existing in the prior art.
[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution:
[0006] A UV-protective automotive window film is prepared by reacting 1-H-pyrrole-3-methanol and pyrrole with allylphosphine dichloride to obtain modified polypyrrole particles; reacting methylcyclotetrasiloxane, octamethylcyclotetrasiloxane, 3-glycidylpropyl(dimethoxy)methylsilane, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to obtain modified polysiloxane; reacting benzo[1,2-d:5,4-d']bis(oxazol)-2,6-dithiol with 4-aminobenzoyl chloride to obtain a modified UV absorber; and reacting isophorone diisocyanate, polytetrahydrofuran ether diol, dibutyltin dilaurate, modified polypyrrole particles, modified polysiloxane, modified UV absorber, and chloroplatinic acid, and then spreading them in a mold to obtain the final product.
[0007] An anti-ultraviolet automotive window film and its preparation method, comprising the following preparation steps:
[0008] (1) Mix polypyrrole particles and tetrahydrofuran at a mass ratio of 1:(40-60), and in a nitrogen atmosphere, in an ice bath, add 0.2-0.4 times the mass of allylphosphine dichloride and 0.1-0.2 times the mass of triethylamine of polypyrrole particles at a rate of 25 μL / min to prepare a solution. Continue stirring for 6-8 h, centrifuge to separate the precipitate, wash the precipitate with deionized water 3-5 times, and freeze-dry for 7-9 h to obtain modified polypyrrole particles;
[0009] (2) Mix isophorone diisocyanate, polytetrahydrofuran ether diol, N,N-dimethylformamide, and dibutyltin dilaurate. Stir at 400-600 r / min for 1.5-2.5 h at 75-85 °C. Add 0.4-0.6 times the mass of modified polypyrrole, 0.2-0.4 times the mass of modified polysiloxane, and 0.1-0.3 times the mass of modified UV absorber. Continue stirring for 2-3 h. Cool to room temperature. Add 0.7-0.9 times the mass of chloroplatinic acid. Discharge the material and spread it evenly in a mold. Let it stand at 80-90 °C for 8-10 h to obtain UV-resistant automotive window film.
[0010] As an optimization, the preparation method of the polypyrrole particles in step (1) is as follows: 1-H-pyrrole-3-methanol and pyrrole are mixed at a mass ratio of 1:6 to obtain a pyrrole monomer mixed solution; ferric chloride hexahydrate, polyacrylol and deionized water are mixed at a mass ratio of 1:(1.2~1.4):(40~60) to obtain the pyrrole monomer mixed solution, stirred at 200~300r / min for 1h at room temperature, placed in an ice bath, and 0.1~0.2 times the mass of ferric chloride hexahydrate pyrrole monomer mixed solution is added, and stirring is continued for 3~5h. The precipitate is separated by centrifugation, and the precipitate is washed with hot water 3~5 times and freeze-dried for 7~9h to obtain the pyrrole monomer mixed solution.
[0011] As an optimization, the preparation method of the modified polysiloxane in step (2) is as follows: Tetramethylammonium hydroxide and octamethylcyclotetrasiloxane are mixed at a mass ratio of 1:(0.2-0.4), and stirred at 200-300 r / min for 1.5-2.5 h under vacuum at 75-85°C to obtain a catalyst; tetramethylcyclotetrasiloxane, octamethylcyclotetrasiloxane, 3-glycidylpropyl(dimethoxy)methylsilane, and 1,3-bis(3-aminopropyl)- 1,1,3,3-Tetramethyldisiloxane was mixed in a molar ratio of 1:(1-2):(0.2-0.4):(1-1.2) to obtain a mixed siloxane; the mixed siloxane and catalyst were mixed in a mass ratio of 1:(0.006-0.009), stirred at 105-115℃ and 200-300 r / min for 6-8 h under a nitrogen atmosphere, the temperature was raised to 140℃, and the reaction was continued for 1-2 h. Low-boiling substances were removed under vacuum at 150℃ to obtain the final product.
[0012] As an optimization, the preparation method of the modified ultraviolet absorber in step (2) is as follows: benzo[…]
[0013] [1,2-d:5,4-d']bis(oxazol)-2,6-dithiol, triethylamine, and tetrahydrofuran were mixed at a mass ratio of 1:(1.2–1.4):(30–40). The mixture was stirred at 200–300 rpm in an ice bath under a nitrogen atmosphere. 4-aminobenzoyl chloride, at a rate of 1–2 mL / min, was added at a rate of 2–3 times the molar amount of benzo[1,2-d:5,4-d']bis(oxazol)-2,6-dithiol. After the addition was complete, the mixture was heated to 45–55 °C and stirred for 7–9 h. The mixture was extracted with ethyl acetate to separate the layers. The organic phase was dried overnight with anhydrous sodium sulfate and rotary evaporated at 30–40 °C for 0.5–1 h. The mixture was then purified by column chromatography using petroleum ether:ethyl acetate at a ratio of 12:1 as the eluent.
[0014] As an optimization, the structural formula of the benzo[1,2-d:5,4-d']bis(oxazol)-2,6-dithiol is:
[0015]
[0016] As an optimization, the mass ratio of isophorone diisocyanate, polytetrahydrofuran ether diol, N,N-dimethylformamide, and dibutyltin dilaurate in step (2) is 1:(4-6):(20-30):(0.4-0.6).
[0017] As an optimization, the polytetrahydrofuran ether diol mentioned in step (2) is a polytetrahydrofuran ether diol with a molecular weight of 2000.
[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0019] In preparing an anti-UV automotive window film, this invention involves reacting 1-H-pyrrole-3-methanol and pyrrole, followed by reaction with allylphosphine dichloride to obtain modified polypyrrole particles; reacting methylcyclotetrasiloxane, octamethylcyclotetrasiloxane, 3-glycidylpropyl(dimethoxy)methylsilane, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to obtain modified polysiloxane; reacting benzo[1,2-d:5,4-d']bis(oxazol)-2,6-dithiol with 4-aminobenzoyl chloride to obtain a modified UV absorber; and reacting isophorone diisocyanate, polytetrahydrofuran ether diol, dibutyltin dilaurate, modified polypyrrole particles, modified polysiloxane, modified UV absorber, and chloroplatinic acid, and then spreading them in a mold to obtain the anti-UV automotive window film.
[0020] First, 1-H-pyrrole-3-methanol and pyrrole are reacted, and then reacted with allylphosphine dichloride to obtain modified polypyrrole particles. Allylphosphine dichloride introduces double bonds on the polypyrrole particles, which can react with the silane-hydrogen bonds on the modified polysiloxane to crosslink, thereby increasing the crosslinking density and effectively improving the tensile strength of the UV-protective automotive window film. Moreover, polypyrrole is an organic conjugated polymer with good near-infrared absorption properties, thus giving the UV-protective automotive window film good heat insulation performance.
[0021] Secondly, modified polysiloxanes were prepared by reacting methylcyclotetrasiloxane, octamethylcyclotetrasiloxane, 3-glycidylpropyl(dimethoxy)methylsilane, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane. The modified polysiloxanes introduced abundant Si-O-Si structures, which have good anti-aging effects, thereby improving the aging resistance of UV-protective automotive window films. Furthermore, the silane-hydrogen bonds on the modified polysiloxanes can chemically crosslink with the double bonds on the modified polypyrrole particles, increasing the crosslinking density and thus improving the tensile strength of the UV-protective automotive window films.
[0022] Finally, a modified UV absorber was prepared by reacting benzo[1,2-d:5,4-d']bis(oxazole)-2,6-dithiol with 4-aminobenzoyl chloride. The UV absorber prepared by the reaction is a thiol ester benzoxazole UV absorber, which has good UV absorption performance and can effectively absorb ultraviolet rays in light, thereby improving the aging resistance and UV protection performance of the UV-protective automotive window film. Detailed Implementation
[0023] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0024] Example 1:
[0025] An anti-ultraviolet automotive window film and its preparation method, comprising the following preparation steps:
[0026] (1) A pyrrole monomer mixed solution was prepared by mixing 1-H-pyrrole-3-methanol and pyrrole at a mass ratio of 1:6; ferric chloride hexahydrate, polyacryl alcohol and deionized water were mixed at a mass ratio of 1:1.2:40, stirred at 200 r / min for 1 h at room temperature, placed in an ice bath, and 0.1 times the mass of ferric chloride hexahydrate pyrrole monomer mixed solution was added. The mixture was stirred for 3 h, and the precipitate was separated by centrifugation. The precipitate was washed three times with hot water and freeze-dried for 7 h to obtain polypyrrole particles.
[0027] (2) Mix polypyrrole particles and tetrahydrofuran at a mass ratio of 1:40. Under a nitrogen atmosphere and an ice bath, add 0.2 times the mass of allylphosphine dichloride and 0.1 times the mass of triethylamine of polypyrrole particles at a rate of 25 μL / min to prepare a solution. Continue stirring for 6 h, centrifuge to separate the precipitate, wash the precipitate with deionized water 3 times, and freeze dry for 7 h to obtain modified polypyrrole particles.
[0028] (3) Tetramethylammonium hydroxide and octamethylcyclotetrasiloxane were mixed at a mass ratio of 1:0.2 and stirred at 200 r / min for 1.5 h under vacuum at 75 °C to obtain a catalyst; tetramethylcyclotetrasiloxane, octamethylcyclotetrasiloxane, 3-glycidylpropyl(dimethoxy)methylsilane, and 1,3-bis(3-aminopropyl)
[0029] -1,1,3,3-Tetramethyldisiloxane was mixed in a molar ratio of 1:1:0.2:1 to obtain a mixed siloxane; the mixed siloxane and catalyst were mixed in a mass ratio of 1:0.006, stirred at 105℃ and 200r / min for 6h under a nitrogen atmosphere, the temperature was raised to 140℃ and the reaction was continued for 1h, and low-boiling substances were removed under vacuum at 150℃ to obtain a modified polysiloxane;
[0030] (4) Benzo[1,2-d:5,4-d']bis(oxazol)-2,6-dithiol, triethylamine, and tetrahydrofuran were mixed at a mass ratio of 1:1.2:30. The mixture was stirred at 200 r / min in an ice bath under a nitrogen atmosphere. 4-aminobenzoyl chloride was added at a rate of 1 mL / min, which was twice the molar amount of benzo[1,2-d:5,4-d']bis(oxazol)-2,6-dithiol. After the addition was complete, the temperature was raised to 45℃ and the stirring was continued for 7 h. The mixture was extracted with ethyl acetate to form layers. The organic phase was dried overnight with anhydrous sodium sulfate and rotary evaporated at 30℃ for 0.5 h. The modified ultraviolet absorber was then separated and purified by chromatographic column separation using petroleum ether:ethyl acetate 12:1 as the eluent.
[0031] (5) Mix isophorone diisocyanate, polytetrahydrofuran ether diol, N,N-dimethylformamide, and dibutyltin dilaurate in a mass ratio of 1:4:20:0.4. Stir at 75°C and 400 r / min for 1.5 h. Add 0.4 times the mass of modified polypyrrole, 0.2 times the mass of modified polysiloxane, and 0.1 times the mass of modified UV absorber. Continue stirring for 2 h. Cool to room temperature and add 0.7 times the mass of chloroplatinic acid. Discharge the material, spread it evenly in a mold, and let it stand at 80°C for 8 h to obtain UV-resistant automotive window film.
[0032] Example 2:
[0033] An anti-ultraviolet automotive window film and its preparation method, comprising the following preparation steps:
[0034] (1) 1-H-pyrrole-3-methanol and pyrrole were mixed at a mass ratio of 1:6 to prepare a pyrrole monomer mixed solution; ferric chloride hexahydrate, polyacryl alcohol and deionized water were mixed at a mass ratio of 1:1.3:50, stirred at room temperature at 250 r / min for 1 h, placed in an ice bath, and 0.15 times the mass of ferric chloride hexahydrate pyrrole monomer mixed solution was added. The mixture was stirred for 4 h, and the precipitate was separated by centrifugation. The precipitate was washed with hot water 4 times and freeze-dried for 8 h to obtain polypyrrole particles.
[0035] (2) Mix polypyrrole particles and tetrahydrofuran at a mass ratio of 1:50. Under a nitrogen atmosphere and an ice bath, add 0.3 times the mass of allylphosphine dichloride and 0.15 times the mass of triethylamine of polypyrrole particles at a rate of 25 μL / min to prepare a solution. Continue stirring for 7 h, centrifuge to separate the precipitate, wash the precipitate with deionized water 4 times, and freeze dry for 8 h to obtain modified polypyrrole particles.
[0036] (3) Tetramethylammonium hydroxide and octamethylcyclotetrasiloxane were mixed at a mass ratio of 1:0.3 and stirred at 250 r / min for 2 h at 80 °C under vacuum to obtain a catalyst; tetramethylcyclotetrasiloxane, octamethylcyclotetrasiloxane, 3-glycidylpropyl(dimethoxy)methylsilane, and 1,3-bis(3-aminopropyl)
[0037] -1,1,3,3-Tetramethyldisiloxane was mixed in a molar ratio of 1:1.5:0.3:1.1 to obtain a mixed siloxane; the mixed siloxane and catalyst were mixed in a mass ratio of 1:0.007, stirred at 110℃ and 250 r / min for 7 h under a nitrogen atmosphere, the temperature was raised to 140℃ and the reaction was continued for 1.5 h, and the low-boiling substances were removed under vacuum at 150℃ to obtain the modified polysiloxane;
[0038] (4) Benzo[1,2-d:5,4-d']bis(oxazol)-2,6-dithiol, triethylamine, and tetrahydrofuran were mixed at a mass ratio of 1:1.3:35. The mixture was stirred at 250 r / min in an ice bath under a nitrogen atmosphere. 4-aminobenzoyl chloride was added at a rate of 1.5 mL / min at a rate of 2.5 times the molar amount of benzo[1,2-d:5,4-d']bis(oxazol)-2,6-dithiol. After the addition was complete, the temperature was raised to 50 °C and the mixture was stirred for 8 h. The mixture was extracted with ethyl acetate to form layers. The organic phase was dried overnight with anhydrous sodium sulfate and rotary evaporated at 35 °C for 0.75 h. The modified ultraviolet absorber was then separated and purified by chromatographic column separation using petroleum ether:ethyl acetate 12:1 as the eluent.
[0039] (5) Mix isophorone diisocyanate, polytetrahydrofuran ether diol, N,N-dimethylformamide, and dibutyltin dilaurate in a mass ratio of 1:5:25:0.5. Stir at 80°C and 500 r / min for 2 h. Add 0.5 times the mass of modified polypyrrole, 0.5 times the mass of modified polysiloxane, and 0.2 times the mass of modified UV absorber. Continue stirring for 2.5 h. Cool to room temperature. Add 0.8 times the mass of chloroplatinic acid. Discharge the material, spread it evenly in a mold, and let it stand at 85°C for 9 h to obtain UV-resistant automotive window film.
[0040] Example 3:
[0041] An anti-ultraviolet automotive window film and its preparation method, comprising the following preparation steps:
[0042] (1) 1-H-pyrrole-3-methanol and pyrrole were mixed at a mass ratio of 1:6 to prepare a pyrrole monomer mixed solution; ferric chloride hexahydrate, polyacryl alcohol and deionized water were mixed at a mass ratio of 1:1.4:60, stirred at 300 r / min for 1 h at room temperature, placed in an ice bath, and 0.2 times the mass of ferric chloride hexahydrate pyrrole monomer mixed solution was added. The mixture was stirred for 5 h, and the precipitate was separated by centrifugation. The precipitate was washed with hot water 5 times and freeze-dried for 9 h to obtain polypyrrole particles.
[0043] (2) Mix polypyrrole particles and tetrahydrofuran at a mass ratio of 1:60. Under a nitrogen atmosphere and an ice bath, add 0.4 times the mass of allylphosphine dichloride and 0.2 times the mass of triethylamine of polypyrrole particles at a rate of 25 μL / min to prepare a solution. Continue stirring for 8 h, centrifuge to separate the precipitate, wash the precipitate with deionized water 5 times, and freeze dry for 9 h to obtain modified polypyrrole particles.
[0044] (3) Tetramethylammonium hydroxide and octamethylcyclotetrasiloxane were mixed at a mass ratio of 1:0.4 and stirred at 300 r / min for 2.5 h at 85 °C under vacuum to obtain a catalyst; tetramethylcyclotetrasiloxane, octamethylcyclotetrasiloxane, 3-glycidylpropyl(dimethoxy)methylsilane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane were mixed at a molar ratio of 1:2:0.4:1.2 to obtain a mixed siloxane; the mixed siloxane and catalyst were mixed at a mass ratio of 1:0.009 and stirred at 300 r / min for 8 h at 115 °C under a nitrogen atmosphere, the temperature was raised to 140 °C and the reaction continued for 2 h, and the low-boiling substances were removed under vacuum at 150 °C to obtain a modified polysiloxane;
[0045] (4) Benzo[1,2-d:5,4-d']bis(oxazol)-2,6-dithiol, triethylamine, and tetrahydrofuran were mixed at a mass ratio of 1:1.4:40. The mixture was stirred at 300 r / min in an ice bath under a nitrogen atmosphere. 4-aminobenzoyl chloride was added at a rate of 2 mL / min at a rate of 3 times the molar amount of benzo[1,2-d:5,4-d']bis(oxazol)-2,6-dithiol. After the addition was complete, the temperature was raised to 55℃ and the stirring was continued for 9 h. The mixture was extracted with ethyl acetate to form layers. The organic phase was dried overnight with anhydrous sodium sulfate and rotary evaporated at 40℃ for 1 h. The modified ultraviolet absorber was then separated and purified by chromatographic column separation using petroleum ether:ethyl acetate 12:1 as the eluent.
[0046] (5) Mix isophorone diisocyanate, polytetrahydrofuran ether diol, N,N-dimethylformamide, and dibutyltin dilaurate in a mass ratio of 1:6:30:0.6. Stir at 85°C and 600 r / min for 2.5 h. Add 0.6 times the mass of modified polypyrrole, 0.4 times the mass of modified polysiloxane, and 0.3 times the mass of modified UV absorber. Continue stirring for 3 h. Cool to room temperature. Add 0.9 times the mass of chloroplatinic acid. Discharge the material, spread it evenly in a mold, and let it stand at 90°C for 10 h to obtain UV-resistant automotive window film.
[0047] Comparative Example 1:
[0048] The difference between the preparation method of the UV-protective automotive window film in Comparative Example 1 and Example 2 is that step (2) is omitted, and step (5) is modified as follows: isophorone diisocyanate, polytetrahydrofuran ether diol, N,N-dimethylformamide, and dibutyltin dilaurate are mixed in a mass ratio of 1:(4-6):(20-30):(0.4-0.6), stirred at 75-85°C and 400-600 r / min for 1.5-2.5 h, and isophorone is added. Add 0.4–0.6 times the mass of polypyrrole particles, 0.2–0.4 times the mass of modified polysiloxane, and 0.1–0.3 times the mass of modified UV absorber to isophorone diisocyanate. Continue stirring for 2–3 hours, cool to room temperature, add 0.7–0.9 times the mass of isophorone diisocyanate, discharge, spread evenly in a mold, and let stand at 80–90°C for 8–10 hours to obtain UV-protective automotive window film. The remaining steps are the same as in Example 2.
[0049] Comparative Example 2:
[0050] The difference between the preparation method of the UV-protective automotive window film in Comparative Example 2 and Example 2 is that steps (1) and (2) are omitted, and step (5) is modified as follows: isophorone diisocyanate, polytetrahydrofuran ether diol, N,N-dimethylformamide, and dibutyltin dilaurate are mixed in a mass ratio of 1:(4-6):(20-30):(0.4-0.6) and stirred at 75-85°C and 400-600 r / min. Mix for 1.5–2.5 hours, then add 0.2–0.4 times the mass of isophorone diisocyanate of modified polysiloxane and 0.1–0.3 times the mass of isophorone diisocyanate of modified UV absorber. Continue stirring for 2–3 hours, cool to room temperature, then add 0.7–0.9 times the mass of isophorone diisocyanate of chloroplatinic acid. Discharge the material, spread it evenly in a mold, and let it stand at 80–90°C for 8–10 hours to obtain UV-protective automotive window film. The remaining steps are the same as in Example 2.
[0051] Comparative Example 3:
[0052] The difference between the preparation method of the UV-protective automotive window film in Comparative Example 3 and Example 2 is that step (3) is omitted, and step (5) is modified as follows: isophorone diisocyanate, polytetrahydrofuran ether diol, N,N-dimethylformamide, and dibutyltin dilaurate are mixed in a mass ratio of 1:(4-6):(20-30):(0.4-0.6) and stirred at 75-85°C and 400-600 r / min for 1 minute. After 5–2.5 hours, add 0.4–0.6 times the mass of isophorone diisocyanate modified polypyrrole particles and 0.1–0.3 times the mass of isophorone diisocyanate modified UV absorber, continue stirring for 2–3 hours, cool to room temperature, add 0.7–0.9 times the mass of isophorone diisocyanate chloroplatinic acid, discharge the material, spread it evenly in a mold, and let it stand at 80–90°C for 8–10 hours to obtain UV-protective automotive window film. The remaining steps are the same as in Example 2.
[0053] Comparative Example 4:
[0054] The difference between the preparation method of the UV-protective automotive window film in Comparative Example 4 and Example 2 is that step (4) is omitted, and step (5) is modified as follows: isophorone diisocyanate, polytetrahydrofuran ether diol, N,N-dimethylformamide, and dibutyltin dilaurate are mixed in a mass ratio of 1:(4-6):(20-30):(0.4-0.6), and stirred at 75-85°C and 400-600 r / min for 1 minute. After stirring for 0.5–2.5 hours, add 0.4–0.6 times the mass of isophorone diisocyanate modified polypyrrole particles and 0.2–0.4 times the mass of isophorone diisocyanate modified polysiloxane. Continue stirring for 2–3 hours, cool to room temperature, add 0.7–0.9 times the mass of isophorone diisocyanate chloroplatinic acid, discharge the material, spread it evenly in a mold, and let it stand at 80–90°C for 8–10 hours to obtain UV-protective automotive window film. The remaining steps are the same as in Example 2.
[0055] Test Example 1:
[0056] Mechanical property testing: Following the test methods in national standard GB / T1040.3-2006, the composite material was cut into dumbbell-shaped strips. The thickness and width of each strip were measured using vernier calipers. The tensile strength of the strips was determined using an electronic universal testing machine. Before testing, the data for the strips to be tested were entered into the computer. The tensile rate was 500 mm / min, and multiple measurements were taken, with the average value recorded. The results are shown in Table 1.
[0057] Aging resistance test: Xenon lamps were used to simulate sunlight. The samples were placed in a xenon lamp accelerated aging test chamber for 360 hours. The experimental atmosphere was air, the temperature was 65℃, the lamp source was 25cm away from the sample, and the radiation intensity was 550W / m². 2 The tensile strength was tested again, and the tensile strength loss rate was calculated as 1 - tensile strength after aging / initial tensile strength. The results are shown in Table 1.
[0058] Table 1
[0059] Example 1 47.35 0.7 Example 2 47.11 0.8 Example 3 47.19 0.8 Comparative Example 1 31.37 0.8 Comparative Example 2 43.83 0.9 Comparative Example 3 33.94 14.1 Comparative Example 4 47.07 27.6
[0060] A comparison of the experimental data from Examples 1-3 and Comparative Examples 1-4 in Table 1 reveals that the UV-resistant automotive window film prepared by this invention has good mechanical properties and aging resistance.
[0061] The difference between Comparative Example 1 and Example 2 is that the polypyrrole particles were not modified with allyl phosphorus dichloride. By comparison, the tensile strength of Examples 1-3 is greater than that of Comparative Example 1, indicating that allyl phosphorus dichloride introduces double bonds on the polypyrrole particles, which can react with the silane-hydrogen bonds on the modified polysiloxane to crosslink, increasing the crosslinking density and effectively improving the tensile strength of the UV-protective automotive window film. The difference between Comparative Example 3 and Example 2 is that no modified polysiloxane was added. By comparison, the tensile strength of Examples 1-3 is greater than that of Comparative Example 3, indicating that the silane-hydrogen bonds on the modified polysiloxane can chemically crosslink with the double bonds on the modified polypyrrole particles, increasing the crosslinking density and thus improving the tensile strength of the UV-protective automotive window film.
[0062] The difference between Comparative Example 3 and Example 2 is that no modified polysiloxane was added. By comparison, the tensile strength loss rate of Examples 1-3 is less than that of Comparative Example 1, indicating that the modified polysiloxane introduces a rich Si-O-Si structure, which has a good anti-aging effect, thereby improving the aging resistance of the UV-resistant automotive window film. The difference between Comparative Example 4 and Example 2 is that no modified UV absorber was added. By comparison, the tensile strength loss rate of Examples 1-3 is less than that of Comparative Example 4, indicating that the modified UV absorber has a good UV absorption effect and can effectively absorb ultraviolet rays in light, thereby improving the aging resistance of the UV-resistant automotive window film.
[0063] Test Example 2:
[0064] UV protection performance test: The UV transmittance of the thin film material was tested using a UV spectrophotometer (UV-1800 Shimadzu). The film to be tested was pre-cut into rectangular slices of 1cm*5cm. Then, the film was placed in the spectrophotometer with tweezers to block the light port for testing. The obtained curve results were converted into CSV format to obtain the final data, and the UV blocking rate was recorded. The results are shown in Table 2.
[0065] Table 2
[0066]
[0067]
[0068] A comparison of the experimental data from Examples 1-3 and Comparative Examples 1-4 in Table 2 reveals that the UV-protective automotive window film prepared by this invention has excellent UV protection performance.
[0069] The difference between Comparative Example 4 and Example 2 is that no modified UV absorber was added. By comparison, the UV blocking rate of Examples 1-3 is greater than that of Comparative Example 1, indicating that the introduction of thiol ester benzoxazole UV absorber gives the anti-UV car window film good UV protection performance.
[0070] Test Example 3:
[0071] Thermal insulation performance test: The thermal insulation performance of the prepared nanocomposite thermal insulation film material was tested using an NS-11 thermal insulation performance tester. A blank glass pane was placed on the left side of the test area, and UV-protected automotive window film was applied. The initial temperatures on both sides were kept the same. The test was conducted by turning on the switch. The temperature difference after 1 minute was recorded. The results are shown in Table 3.
[0072] Table 3
[0073] Example 1 1.8 Comparative Example 1 1.9 Example 2 1.7 Comparative Example 2 5.2 Example 3 1.9 Comparative Example 3 1.8 Comparative Example 4 2.0
[0074] A comparison of the experimental data from Examples 1-3 and Comparative Examples 1-4 in Table 3 reveals that the UV-resistant automotive window film prepared by this invention has excellent heat insulation performance.
[0075] The difference between Comparative Example 2 and Example 2 is that no modified polypyrrole particles were added. By comparison, the temperature difference between Examples 1 and 3 was significantly smaller than that between Comparative Example 2, indicating that the modified polypyrrole particles introduced polypyrrole into the UV-protective automotive window film. Polypyrrole is an organic conjugated polymer with good near-infrared absorption properties, which makes the UV-protective automotive window film have good heat insulation properties.
[0076] Test Example 4:
[0077] Flame retardant performance test: Samples of the UV-resistant automotive window films obtained from each embodiment and test example were prepared according to GB / T2406 and the limiting oxygen index was tested. The results are shown in Table 4.
[0078] Table 4
[0079] Example 1 37.2 Comparative Example 1 24.7 Example 2 37.5 Comparative Example 2 24.1 Example 3 37.4 Comparative Example 3 31.8 Comparative Example 4 37.2
[0080] A comparison of the experimental data from Examples 1-3 and Comparative Examples 1-4 in Table 4 reveals that the UV-resistant automotive window film prepared by this invention has good flame-retardant properties.
[0081] The difference between Comparative Example 1 and Example 2 is that the polypyrrole particles were not modified with allyl phosphorus dichloride. By comparison, the limiting oxygen index of Examples 1 to 3 is significantly greater than that of Comparative Example 1, indicating that allyl phosphorus dichloride introduces abundant phosphorus elements into the UV protection car film, which can promote char formation during combustion and effectively improve the flame retardant performance of the UV protection car film.
[0082] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A UV-protective automotive window film, characterized in that, The UV-protective automotive window film is prepared by reacting isophorone diisocyanate, polytetrahydrofuran ether diol, dibutyltin dilaurate, modified polypyrrole particles, modified polysiloxane, modified UV absorber, and chloroplatinic acid, and then spreading them in a mold. The modified polypyrrole particles were prepared by reacting 1-H-pyrrole-3-methanol and pyrrole with allylphosphine dichloride. The modified polysiloxane is prepared by reacting methylcyclotetrasiloxane, octamethylcyclotetrasiloxane, 3-glycidylpropyl(dimethoxy)methylsilane, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane. The modified UV absorber is prepared by reacting benzo[1,2-d:5,4-d']bis(oxazol)-2,6-dithiol with 4-aminobenzoyl chloride.
2. A method for preparing the UV-protective automotive window film as described in claim 1, characterized in that, The preparation steps include the following: (1) Mix polypyrrole particles and tetrahydrofuran at a mass ratio of 1: (40~60). Under a nitrogen atmosphere, in an ice bath, add 0.2~0.4 times the mass of allylphosphine dichloride and 0.1~0.2 times the mass of triethylamine of polypyrrole particles at a rate of 25 μL / min to prepare a solution. Continue stirring for 6~8 h, centrifuge to separate the precipitate, wash the precipitate with deionized water 3~5 times, and freeze-dry for 7~9 h to obtain modified polypyrrole particles; (2) Mix isophorone diisocyanate, polytetrahydrofuran ether diol, N,N-dimethylformamide and dibutyltin dilaurate, stir at 75~85℃ and 400~600r / min for 1.5~2.5h, add 0.4~0.6 times the mass of isophorone diisocyanate of modified polypyrrole, 0.2~0.4 times the mass of isophorone diisocyanate of modified polysiloxane, and 0.1~0.3 times the mass of isophorone diisocyanate of modified UV absorber, continue stirring for 2~3h, cool to room temperature, add 0.7~0.9 times the mass of isophorone diisocyanate of chloroplatinic acid, discharge the material, spread it evenly in a mold, and let it stand at 80~90℃ for 8~10h to obtain UV-resistant automotive window film.
3. The method for preparing the UV-protective automotive window film according to claim 2, characterized in that, The preparation method of the polypyrrole particles in step (1) is as follows: 1-H-pyrrole-3-methanol and pyrrole are mixed at a mass ratio of 1:6 to obtain a pyrrole monomer mixed solution; ferric chloride hexahydrate, polyacryl alcohol and deionized water are mixed at a mass ratio of 1:(1.2~1.4):(40~60) to obtain the pyrrole monomer mixed solution. The mixture is stirred at 200~300r / min for 1h at room temperature, placed in an ice bath, and 0.1~0.2 times the mass of ferric chloride hexahydrate pyrrole monomer mixed solution is added. The mixture is stirred for 3~5h, centrifuged to separate the precipitate, and the precipitate is washed with hot water 3~5 times and freeze-dried for 7~9h to obtain the pyrrole monomer mixed solution.
4. The method for preparing the UV-protective automotive window film according to claim 2, characterized in that, The modified polysiloxane in step (2) is prepared as follows: Tetramethylammonium hydroxide and octamethylcyclotetrasiloxane are mixed at a mass ratio of 1:(0.2~0.4), and stirred at 200~300 r / min for 1.5~2.5 h under vacuum at 75~85℃ to obtain a catalyst; tetramethylcyclotetrasiloxane, octamethylcyclotetrasiloxane, 3-glycidylpropyl(dimethoxy)methylsilane, and 1,3-bis(3-aminopropyl)-1, 1,3,3-Tetramethyldisiloxane was mixed in a molar ratio of 1:(1~2):(0.2~0.4):(1~1.2) to obtain a mixed siloxane; the mixed siloxane and catalyst were mixed in a mass ratio of 1:(0.006~0.009), stirred at 105~115℃ and 200~300r / min for 6~8h under a nitrogen atmosphere, heated to 140℃ and continued to react for 1~2h, and the low-boiling substances were removed under vacuum at 150℃ to obtain the final product.
5. The method for preparing the anti-ultraviolet automotive window film according to claim 2, characterized in that, The modified UV absorber described in step (2) is prepared as follows: Benzo[1,2-d:5,4-d']bis(oxazol)-2,6-dithiol, triethylamine, and tetrahydrofuran are mixed at a mass ratio of 1:(1.2~1.4):(30~40). Under a nitrogen atmosphere, in an ice bath, the mixture is stirred at 200~300 r / min. 4-aminobenzoyl chloride, which is 2~3 times the molar amount of benzo[1,2-d:5,4-d']bis(oxazol)-2,6-dithiol, is added at a rate of 1~2 mL / min. After the addition is complete, the temperature is raised to 45~55℃ and the mixture is stirred for 7~9 h. The mixture is extracted with ethyl acetate to form layers. The organic phase is dried overnight with anhydrous sodium sulfate and rotary evaporated at 30~40℃ for 0.5~1 h. The mixture is then separated and purified by chromatographic column separation using petroleum ether:ethyl acetate 12:1 as the eluent.
6. The method for preparing the UV-protective automotive window film according to claim 2, characterized in that, The mass ratio of isophorone diisocyanate, polytetrahydrofuran ether diol, N,N-dimethylformamide, and dibutyltin dilaurate in step (2) is 1:(4~6):(20~30):(0.4~0.6).
7. The method for preparing the UV-protective automotive window film according to claim 2, characterized in that, The polytetrahydrofuran ether diol mentioned in step (2) is a polytetrahydrofuran ether diol with a molecular weight of 2000.
Citation Information
Patent Citations
Benzo [1, 2-d: 5, 4-d']-di-(oxazole)-2, 6-dithiol and preparation method thereof
CN104098590A